Augmentasi tulang alveolar dengan osteogenesis distraksi Alveolar ridge augmentation using distraction osteogenesis - Siti Sarah Aulia Amrullah; Rosida Sani; Nurfadhilah Arifin; Muhammad Ruslin (Journal of Dentomaxillofacial Science, 2012)
Augmentation of the alveolar ridge is widely performed in implant treatment to create predictable function andesthetics in area with inadequate bone volume. There are some different ways to augment the alveolar ridge.Distraction osteogenesis is a new method in increasing the width of the ridge and preparing a sufficient bed for implantor prosthesis. Distraction osteogenesis result in formation of new bone between bone segments that are separatedgradually by incremental traction. Alveolar widening by distraction osteogenesis is an alternative method forreconstructing alveolar atrophy that is similar to alveolar split grafting but without grafting, which offers manyadvantages over traditional techniques. This paper is aimed to discuss considerations and technique of alveolar ridgeaugmentation for preparing adequate bone volume before applying implant by using distraction osteogenesistechnique.